Analysis of The Quality of Population Administration Services - Helmie Maulia Wati; Hendra Sukmana (Indonesian Journal of Public Policy Review, 2022)
This study aims to analyze and describe the quality of population administration services in Kajeksan Village, Strengthening District, Sidoarjo Regency. This research is based on the fact that in providing population administration management services, of course, there are problems. Which takes one week to process an ID card, but in reality it takes up to 2 weeks. This research method uses descriptive qualitative, data collection is done by in-depth interviews, observation and review of relevant literature. The technique of determining the informant uses purposive sampling. The informants in this study were the head of the Kajeksan village, the secretary of the Kajeksan village, the head of the TU and the general public and 2 users of population administration services. The analysis technique in this study is a qualitative analysis type, referring to the theory of Miles and Huberman. The results showed that, Analysis of the quality of population administration services in Kejeksan village, Tulangan sub-district, Sidoarjo district. On time guarantees that have not provided satisfaction to the community as service users, it is necessary to arrange a schedule for service officers so that they can be in place, so that people can quickly get services.